Obesity Indices for Predicting Functional Fitness in Children and Adolescents With Obesity - Kanokporn Udomittipong; Teerapat Thabungkan; Akarin Nimmannit; Prakarn Tovichien; Pawinee Charoensitisup; Khunphon Mahoran (Frontiers Media S.A., 2021)
Objectives: We aimed to determine the obesity indices that affect 6-min walk test (6-MWT) distance in children and adolescents with obesity and to compare the 6-MWT distance of obese subjects with that of normal-weight subjects.Methods: Obese children and adolescents aged 8-15 years and normal-weight age- and gender-matched controls were enrolled. All participants performed the 6-MWT; respiratory muscle strength (RMS), including maximal inspiratory pressure and maximal expiratory pressure; and spirometry. Data between groups were compared. In the obesity group, correlation between obesity indices and pulmonary function testing (6-MWT, RMS, and spirometry) was analyzed.Results: The study included 37 obese and 31 normal-weight participants. The following parameters were all significantly lower in the obesity group than in the normal-weight group: 6-MWT distance (472.1 ± 66.2 vs. 513.7 ± 72.9 m; p = 0.02), forced expiratory volume in one second/forced vital capacity (FEV1/FVC) (85.3 ± 6.7 vs. 90.8 ± 4.5%; p < 0.001), forced expiratory flow rate within 25-75% of vital capacity (FEF25−75%) (89.8 ± 23.1 vs. 100.4 ± 17.3 %predicted; p = 0.04), and peak expiratory flow (PEF) (81.2 ± 15 vs. 92.5 ± 19.6 %predicted; p = 0.01). The obesity indices that significantly correlated with 6-MWT distance in obese children and adolescents were waist circumference-to-height ratio (WC/Ht) (r = −0.51; p = 0.001), waist circumference (r = −0.39; p = 0.002), body mass index (BMI) (r = −0.36; p = 0.03), and chest circumference (r = −0.35; p = 0.04). WC/Ht was the only independent predictor of 6-MWT distance by multiple linear regression.Conclusions: Children and adolescents with obesity had a significantly shorter 6-MWT distance compared with normal-weight subjects. WC/Ht was the only independent predictor of 6-MWT distance in the obesity group.